1985
DOI: 10.1093/jac/15.suppl_a.221
|View full text |Cite
|
Sign up to set email alerts
|

Use of an in-vitro kinetic model to study antibiotic combinations

Abstract: A two compartment pharmacokinetic model was used to study combinations of piperacillin with N-formimidoyl thienamycin or amikacin, and azlocillin with netilmicin against strains of Pseudomonas aeruginosa. Antibiotic antagonism seen with in-vitro static tests of piperacillin and thienamycin did not occur with the kinetic model. Piperacillin plus amikacin showed enhanced activity, and azlocillin prevented bacterial regrowth seen with netilmicin alone during multiple dosing experiments at high bacterial inocula. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The model can be used for simulation of both continuous and intermittent drug administration (13). Simultaneous first order elimination kinetics of two drugs with different half-lives were simulated to study antibacterial effects of drug combinations (120,119,14).…”
Section: Models With Variable Antibiotic Concentrationsmentioning
confidence: 99%
“…The model can be used for simulation of both continuous and intermittent drug administration (13). Simultaneous first order elimination kinetics of two drugs with different half-lives were simulated to study antibacterial effects of drug combinations (120,119,14).…”
Section: Models With Variable Antibiotic Concentrationsmentioning
confidence: 99%
“…Linezolid (16 g/ml) was used to simulate clinically achievable peak serum concentrations in patients administered 600 mg every 12 h (q12h) (10). Additionally, a previously described one-compartment in vitro pharmacodynamic model (IVPM) provided continuous exposure of bacteria to changing concentrations of antibiotics (3,29). All model simulations were conducted over 48 h and were performed at minimum in triplicate.…”
mentioning
confidence: 99%
“…In an in vitro pharmacokinetic model, Zinner et al [1985] concluded that the am inoglycoside had an immediate effect and reduced the concentration of viable bacte ria by three decades in 2 h. However, bac terial regrowth started after 6 h and subse quent aminoglycoside doses had no effect. With a P-lactam combination regimen, rapid bacterial killing was not followed by bacterial regrowth [Zinner and Dudley, 1986].…”
Section: Discussionmentioning
confidence: 99%